SURVEY OF EDIBLE FOREST INSECTS UTILIZED BY THE PEOPLE IN SOUTH WEST NIGERIA - OJ, OLUJOBI; MA, ABDULSALAM (Innovare Journal of Agricultural Sciences, 2022)
This study was conducted to take inventory of edible forest insects and evaluate their contributions to the livelihood of the people of southwest Nigeria. Multi-stage sampling technique was used to select three states (Lagos, Ogun and Kwara). Four towns were selected in each of the states while five respondents were randomly selected from each town. Sixty (60) Pre-tested semi-structured questionnaire was administered to selected respondents in the study area. Data collected were analyzed using descriptive statistics. The study showed that majority of the respondents are married (53.4 %), female (61.7 %) with (75 %) having at least secondary education. The study also revealed that 10 different insects were collected and utilized for various purposes by the respondents with Macrotermes bellicosus and Apis mellifera being the most sort after insects, (18.2 %) each, while 66.7 % of the respondents collect/harvest their products during raining season mostly by hunting (30.1 %). Majority (70.7 %) of the respondents generate over ₦20,000 from sales of edible insects annually, while 21.5 % of the respondents opined that seasonal availability and irritating physical structure are the major constraints militating against the consumption of edible insects in the study area. Avoiding deforestation and indiscriminate forest fire were the major conservation measures suggested by the respondents. It was recommended that government should enforce legislation against bush burning and illegal felling of trees.